The Big Bang and Theology - Pitts, J. Brian (Zygon, 2025)
This article extends and clarifies a case previously made that the cosmic singularity provides negligible support for creation and hence theism. A key task is to provide a modally robust notion of beginning to yield a valid argument. A physical theory might have no metric or multiple metrics, so a beginning, to avoid conventionality, equivocation, and modal provincialism, should imply a lack of past maximal extension, whereas Big Bang models are past maximally extended. The mathematical analogy between the Big Bang and stellar gravitational collapse indicates that the former requires a Creator only if the latter requires a Destroyer. Gravitational thermodynamics, though making rapid progress, is still immature, making it questionable whether thermodynamic arguments against eternal cosmological models will survive. Recent philosophical discussion of the opaque justification of maximal extension toward the past is noted and related to other themes in philosophy and science-religion literature such as rationalism versus empiricism.